2022
DOI: 10.30762/jeels.v8i1.222
|View full text |Cite
|
Sign up to set email alerts
|

Face-To-Face Or Online Speaking Practice: A Comparison of Students’ Foreign Language Classroom Anxiety Level

Abstract: Speaking using foreign language in front of other people can be one of the most anxiety-provoking situations. Learners who does not enjoy interacting with other people or being the center of attention may exhibit extreme anxiety when they are asked to take parts in oral presentation, discussion, or any other kind of language activities. A study found that online discussion may decrease the effect. It provides a non-threatening situation for learners who are shy and withdrawn. This survey study aims to see whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The fourth, although this research also mentions CLT, it is not in the context of learning English in Indonesia (Ng, 2020). Finally, a study by Yaniafari and Rihardini (2021) has used a quantitative method (questionnaire) with samples taken from two different types of classes; Speaking for public purposes and speaking for academic purposes which are very different from the current research.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The fourth, although this research also mentions CLT, it is not in the context of learning English in Indonesia (Ng, 2020). Finally, a study by Yaniafari and Rihardini (2021) has used a quantitative method (questionnaire) with samples taken from two different types of classes; Speaking for public purposes and speaking for academic purposes which are very different from the current research.…”
Section: Introductionmentioning
confidence: 88%
“…For instance, there is the software application such as zoom in online learning for prospective teachers in which the CLT approach is used to mediate the learning system (Ng, 2020). In fact, in the practice of speaking as an interaction, it was found that the intensity of student anxiety when practicing speaking tends to be lower in online learning compared to face-toface meeting (Yaniafari & Rihardini, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One advantage is that it removes boundaries, allows students to learn without time and place constraints, and facilitates ubiquitous learning (Ashar et al, 2020). Besides, virtual classes foster interactive activities (Kim & Bennekin, 2013), enhance motivation (Islam et al, 2018), and reduce anxiety (Bakar et al, 2013;Yaniafari & Rihardini, 2021). Aydin (2008) argues that e-learning might enhance students' interaction due to the motivation and encouragement created by online applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaisar & Chowdury (2020) argue that language learners experience anxiety in online classes when they worry about being left behind and unable to follow the changes in their communication models optimally. However, online learning reduces the intimidating and stressful atmosphere for communication during the language learning process (Yaniafari & Rihardini, 2021).…”
mentioning
confidence: 99%
“…Foreign language anxiety sources in online learning may appear as new extents, or they may also be similar to conventional learning settings. Yaniafari and Rihardini (2021) state that the main anxiety source reported in online learning is the fear of being laughed at and the fear of making mistakes, which resembles the conventional learning setting.…”
mentioning
confidence: 99%